Novel irreversible electroporation ablation (Nano-knife) versus radiofrequency ablation for the treatment of solid liver tumors: a comparative, randomized, multicenter clinical study - Zhang, Xiaobo; Zhang, Xiao; Ding, Xiaoyi; Wang, Zhongmin; Fan, Yong; Chen, Guang; Hu, Xiaokun; Zheng, Jiasheng; Xue, Zhixiao; He, Xiaofeng; Zhang, Xin; Wei, Yingtian; et al. (Frontiers in Oncology, 2022)
Irreversible electroporation (IRE) is a soft tissue ablation technique that uses short electrical fields which induce the death of target cells. To evaluate the safety and efficacy of an IRE-based device compared to regular radiofrequency ablation (RFA) of solid liver tumors, in this multicenter, randomized, parallel-arm, non-inferiority study, 152 patients with malignant liver tumors were randomized into IRE (n = 78) and RFA (n = 74) groups. The primary endpoint was the success rate of tumor ablation; the secondary endpoints included the tumor ablation time, complications, tumor recurrence rates and treatment-related adverse events (TRAE). The success rate of tumor ablation using IRE was 94.9% and was non-inferior to the RFA group (96.0%) (P = 0.761). For the secondary endpoints, the average ablation time was 34.29 ± 30.38 min for the IRE group, which was significantly longer than for the RFA group (19.91 ± 16.08 min) (P < 0.001). The incidences of postoperative complications after 1 week (P = 1.000), 1 month (P = 0.610) and 3 months (P = 0.490) were not significantly different between the 2 groups. The recurrence rates of liver tumor at 1, 3 and 6 months after ablation were 0 (0.0%), 10 (13.9%) and 10 (13.3%) in the IRE group and 2.9%, 7.3% and 19.7% in the RFA control group (all P > 0.05), respectively. For safety assessments, 51 patients experienced 191 AEs (65.4%) in the IRE group, which was not different from the RFA group (73.0%, 54/184) (P = 0.646). In 7 IRE patients, 8 TRAEs (7.9%) occurred, the most common being edema of the limbs (mild grade) and fever (severe grade), while no TRAEs occurred in the RFA group. This study proved that the excellent safety and efficacy of IRE was non-inferior to the regular radiofrequency device in ablation performance for the treatment of solid liver tumors. Clinical trial registration: Chinese Clinical Trial Registry: ChiCTR1800017516